Ethnobotanical study on traditional medicinal plants used by Oromo ethnic people of Goro district, Bale zone of Oromia region, Ethiopia - Usman, Kedir Adem; Egigu, Meseret C.; Mahalingam, J. Sasikumar (Ethnobotany Research and Applications, 2022)
Background: An ethnobotanical study was conducted among Oromo people in Goro district, Oromia region, Ethiopia to document ethnomedicinal uses of plants. Methods: Semi-structured interviews, focus group discussion and field walks were used to collect data on medicinal plants and demography during October 2017- September 2018 from 369 non-traditional and 24 traditional medicine practitioners. Descriptive statistics and quantitative indices viz. Independent t-test, Analysis of Variance (ANOVA), multiple regression analysis, Informant Consensus Factor (ICF), Fidelity Level (FL), Preference Ranking (PR) and Direct Matrix Ranking (DMR) were performed to analyze the data. Results: A total of 84 medicinal plants belonging to 45 families were documented. The family Asteraceae was represented by six species. Most of the plants were herbs (30). The most frequently used plant parts were leaves (39.36%) followed by roots (19.18%). Oral route was frequently (62.26%) cited way of remedy application. Gastrointestinal and Dermatological illnesses had the highest ICF value (0.80), whereas the least ICF value was for Parasitic infections (0.47).The highest FL (100%) was recorded for Aloe ruspoliana and Nicotiana tabacum for Wound and Leech repulsion, respectively. Achyranthes aspera was top-ranked plant to treat stomachache. The analysis of DMR revealed Cordia africana as top-ranked multipurpose plant. Gender, age and educational status significantly (p<0.05) affected the traditional medicinal knowledge. Results of multiple linear regression showed that age and educational status predicted traditional medicinal knowledge. Conclusion: Our study explored the profound indigenous knowledge of the Oromo people of the study area. Their traditional knowledge on the medicinal plants must be validated with phytochemical and pharmacological studies and the knowledge needs to be preserved. Keywords: Direct matrix ranking, Fidelity level, Goro district, Informant consensus factor, Preference ranking, Traditional medicine